2020
DOI: 10.1101/2020.08.11.245100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ambroxol and Ciprofloxacin Show Activity Against SARS-CoV2 in Vero E6 Cells at Clinically-Relevant Concentrations

Abstract: We studied the activity of a range of weakly basic and moderately lipophilic drugs against SARS CoV2 in Vero E6 cells, using Vero E6 survival, qPCR of viral genome and plaque forming assays. No clear relationship between their weakly basic and hydrophobic nature upon their activity was observed. However, the approved drugs ambroxol and ciprofloxacin showed potent activity at concentrations that are clinically relevant and within their known safety profiles, and so may provide potentially useful agents for prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
(34 reference statements)
1
9
0
Order By: Relevance
“…Another recent study by Olaleye et al (21) specifically analyzed the effects of Bromhexine and Ambroxol on the interaction of ACE2 with the SARS-CoV-2 spike receptor binding domain (RBD), and reported a very peculiar behavior of these substances which in part may explain the paradoxic results of our fusion assays and would support a beneficial effect of low-dose Bromhexine, which is converted to Ambroxol in vivo : While Ambroxol weakly inhibited the ACE2-RBD interaction up to 100μM concentration, Bromhexine exhibited a biphasic behavior and was weakly inhibitory below 10μM but increased ACE2-RBD binding at higher concentrations in that study. Both substances were reported to weakly inhibit SARS-CoV-2-mediated cytopathic effect in culture (22), and Ambroxol was also shown to moderately impact replication of SARS-CoV-2 in that report (22), albeit on Vero cells and not lung cells. Our results suggest that Ambroxol can weakly inhibit spike-driven entry of lentiviral pseudotypes into Calu-3 cells at high but potentially attainable concentrations (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another recent study by Olaleye et al (21) specifically analyzed the effects of Bromhexine and Ambroxol on the interaction of ACE2 with the SARS-CoV-2 spike receptor binding domain (RBD), and reported a very peculiar behavior of these substances which in part may explain the paradoxic results of our fusion assays and would support a beneficial effect of low-dose Bromhexine, which is converted to Ambroxol in vivo : While Ambroxol weakly inhibited the ACE2-RBD interaction up to 100μM concentration, Bromhexine exhibited a biphasic behavior and was weakly inhibitory below 10μM but increased ACE2-RBD binding at higher concentrations in that study. Both substances were reported to weakly inhibit SARS-CoV-2-mediated cytopathic effect in culture (22), and Ambroxol was also shown to moderately impact replication of SARS-CoV-2 in that report (22), albeit on Vero cells and not lung cells. Our results suggest that Ambroxol can weakly inhibit spike-driven entry of lentiviral pseudotypes into Calu-3 cells at high but potentially attainable concentrations (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Ambroxol may also exhibit weak but broad anti-viral activity as it was shown to reduce the occurrence of respiratory infections (17) and to inhibit proteolytic activation of influenza virus by triggering release of antiviral factors (18), and it is used to treat acute respiratory distress syndrome in adults and antenatally in infants (19, 20). Further, two recent preprints, one describing modulation of the ACE2-SARS2-S interaction by both Bromhexine and Ambroxol (21) and the other reporting weak inhibitory activity of Ambroxol against SARS-CoV-2 replication (22) in Vero E6 cells, point at a potential utility of these molecules in the therapy of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Our study is supported by two pre-published studies. A study by Bradfute et al demonstrated that ambroxol blocks Vero-E6 cells infection with SARS-CoV-2 ( 38 ). A study by Olaleye et al revealed that micromolar concentrations of ambroxol prevented cellular infections with SARS-CoV-2 determined as cytopathic effect of the virus ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…et. al 49 ., in which they reported that AMB could inhibit SARS-CoV-2 infection in vitro at high concentrations 49 . Our biochemical findings are most complementary to the report by Hornich, B.F. et.…”
Section: Discussionmentioning
confidence: 97%
“…The IC 50 values that we observed for the reference compounds are consistent with earlier reports [44][45][46][47] . While writing this manuscript, we found that other cellular studies tested BHH and AMB at certain or single concentrations [48][49][50] ; however, this is the first study to our knowledge to conduct the IC 50 evaluation for BHH and AMB against the novel SARS-CoV-2 infection induced CPE.…”
Section: Sars-cov-2 Infection Induced Cytopathic Effect (Cpe) In Veromentioning
confidence: 99%